2017
DOI: 10.1089/jmf.2017.3916
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Piceatannol, a Natural Stilbene, in Metabolic Diseases: A Review

Abstract: Metabolic disease comprises a set of risk factors highly associated with obesity and insulin resistance and is a consequence of central adiposity, hyperglycemia, and dyslipidemia. Furthermore, obesity increases the risk of the development of metabolic disease due to ectopic fat deposition, low-grade inflammation, and systemic energy disorders caused by dysregulated adipose tissue function. Piceatannol is a naturally occurring polyphenolic stilbene found in various fruits and vegetables and has been reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 86 publications
2
69
0
4
Order By: Relevance
“…Using the enzyme kinetic parameters for RHA and ISO formation in HLC found in this study, fractions metabolized (fm); f m h,OMT,RHA and f m h,OMT,ISO in humans were calculated to be 66.6% ± 15.4% and 13.2% ± 3.3% respectively. Clearly, besides glucuronidation and sulfation, O ‐methylation was also one of the major hepatic metabolic pathways of PIC. Of note, when RES was incubated in the same reaction system, neither pinostilbene ( trans ‐3,4′‐dihydroxy‐5‐methoxystilbene) nor desoxyrhapontigenin (4‐methoxyresveratrol or trans ‐3,5‐dihydroxy‐4′‐methoxystilbene) was detected, confirming a lack of O ‐methylation in the metabolism of RES.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the enzyme kinetic parameters for RHA and ISO formation in HLC found in this study, fractions metabolized (fm); f m h,OMT,RHA and f m h,OMT,ISO in humans were calculated to be 66.6% ± 15.4% and 13.2% ± 3.3% respectively. Clearly, besides glucuronidation and sulfation, O ‐methylation was also one of the major hepatic metabolic pathways of PIC. Of note, when RES was incubated in the same reaction system, neither pinostilbene ( trans ‐3,4′‐dihydroxy‐5‐methoxystilbene) nor desoxyrhapontigenin (4‐methoxyresveratrol or trans ‐3,5‐dihydroxy‐4′‐methoxystilbene) was detected, confirming a lack of O ‐methylation in the metabolism of RES.…”
Section: Resultsmentioning
confidence: 99%
“…Piceatannol ( trans ‐3,5,3′,4′‐tetrahydroxystilbene, PIC) is a polyphenol present in various edible plants such as blueberries, grape, passion fruit, and peanut . Similar to its precursor resveratrol ( trans ‐3,5,4′‐trihydroxystilbene, RES), one of the most well‐known nutraceuticals PIC displayed health‐promoting activities including anti‐ageing, anti‐cancer, anti‐diabetic, anti‐inflammation, anti‐obesity, anti‐oxidation, cardio‐, hepato‐, nephro‐, and neuro‐protection in many pre‐clinical studies . Moreover, in various previous studies, PIC displayed pharmacological potencies superior to RES .…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has been well studied in prevention and treatment of various kinds of metabolic disorders [ 34 ], and in our previous study, we have reported the anti-angiogenic activities of resveratrol [ 29 ]. However, relatively low oral bioavailability is a major barrier of resveratrol for human consumption: resveratrol is metabolized extensively, and its oral bioavailability has been estimated to be less than 1.0% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous animal studies, researches on PIC mainly focused on metabolic diseases. 31 For example, Uchida-Maruki et al 32 applied PIC to mice on high-fat diet, and found that PIC not only did not affect visceral fat gain or weight gain in mice, but also reduced the fasting glucose level of mice, suggesting that PIC might have application value in the prevention of diabetes. In addition, PIC has been reported to inhibit the invasion of hepatocellular carcinoma cell by scavenging intracellular reactive oxygen species, and restrain the growth and metastasis of solid tumors in mouse models with hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%